2003
DOI: 10.2166/wst.2003.0280
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic response of biofilm to pipe surface and fluid velocity

Abstract: Biofouling in pipelines is a function of the inner roughness of the specific piping material that is used in distribution systems and the concomitant biofilm formation. To test the effect of velocity on the growth of biofilm, a Roto-Scope was designed and built to imitate different materials and flow conditions in potable water distribution systems. Biofilm formation was monitored using DAPI staining and the total number of viable bacteria. Increased velocity in the system resulted in a specific detaching velo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
27
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(30 citation statements)
references
References 9 publications
3
27
0
Order By: Relevance
“…The same study showed that there was no significant difference in the viable counts on PE and PVC. Different results were obtained by Cloete et al (2003), where biofilm formation was higher on the PVC surfaces than on galvanized steel piping. van der Kooij and Veenendaal (2001) and Clark et al (1994) observed that PE supports biofilm formation in a higher degree than PVC, while Wingender and Flemming (2004), Pedersen (1990) and Zacheus et al (2000) concluded that there was no significant difference in the colonization of the investigated materials (stainless steel, PVC and PE), in some cases after decades of operation.…”
Section: Article In Pressmentioning
confidence: 76%
See 1 more Smart Citation
“…The same study showed that there was no significant difference in the viable counts on PE and PVC. Different results were obtained by Cloete et al (2003), where biofilm formation was higher on the PVC surfaces than on galvanized steel piping. van der Kooij and Veenendaal (2001) and Clark et al (1994) observed that PE supports biofilm formation in a higher degree than PVC, while Wingender and Flemming (2004), Pedersen (1990) and Zacheus et al (2000) concluded that there was no significant difference in the colonization of the investigated materials (stainless steel, PVC and PE), in some cases after decades of operation.…”
Section: Article In Pressmentioning
confidence: 76%
“…In most fixed biomass systems, stable and higher flow rates have the advantage of limiting biofilm growth (Peyton and Characklis, 1993;Melo and Vieira, 1999;Cloete et al, 2003), since they produce thinner and more cohesive layers less prone to release bacteria into the bulk water. However, these conditions are not always feasible to maintain in drinking water networks.…”
Section: Introductionmentioning
confidence: 99%
“…The results obtained for coaggregation and community population dynamics therefore can be considered to relate to occurrences within polymicrobial freshwater communities. Shear rates have been suggested to be important in the development of biofilm community structure (3) and govern the abilities of individual species to immigrate to biofilms and to colonize new surfaces (9,45). Other factors include substratum composition, concentrations of solutes, and nutrient availability (6,19).…”
Section: Discussionmentioning
confidence: 99%
“…Few published articles have described the effect of shear on the bacterial composition and diversity of freshwater biofilms. Evidence is emerging, however, that at high fluid velocities with associated high shear rates, multispecies communities are less diverse than those developed at lower shear rates (9,23,35,42). In order to adhere to surfaces or surface-attached cells and subsequently to form biofilms, bacteria in high-velocity flowing systems must overcome shear stress at the fluid-surface interface (7, 11).…”
mentioning
confidence: 99%
“…The formation of biofilms increases with the flow velocity of water due to the increase of nutrient mass transfer [15]. Nevertheless, specific velocities between 3-4 m/s may favor its release [4].…”
Section: Case-studymentioning
confidence: 99%